2016
DOI: 10.1590/2317-1545v38n3165298
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical aspects of castor beans seeds deterioration stored in different packaging conditions and temperatures

Abstract: -The present study aimed to evaluate effects of different storage conditions on the castor bean seed cultivar IAC-226 quality, stored for 12 months. For this purpose, seeds were stored in different environment and packaging conditions: in a cold chamber and conventional storage, using multiwall Kraft paper and in no vacuum and vacuum plastic packages at 1 atm; as well as under cryopreservation storage (-196 °C). Seed quality was evaluated before and after 4, 8 and 12 months of storage by germination tests, fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…However, the germination percentage of IAC-80 seeds stored in the other conditions decreased with storage time. These results denote the effect of the storage condition on the preservation of viability of R. communis seeds, as reported by Santos et al (2016), who evaluated the conservation of R. communis seeds in conventional, and cold room conditions for twelve months.…”
supporting
confidence: 82%
See 4 more Smart Citations
“…However, the germination percentage of IAC-80 seeds stored in the other conditions decreased with storage time. These results denote the effect of the storage condition on the preservation of viability of R. communis seeds, as reported by Santos et al (2016), who evaluated the conservation of R. communis seeds in conventional, and cold room conditions for twelve months.…”
supporting
confidence: 82%
“…Therefore, the cryopreservation of R. communis seeds enabled a long-term conservation. Similarly, Santos et al (2016) The first germination count of Guarani seeds showed significant differences within the storage periods ( Table 3). The seed germination percentage in the first count increased up to four months and remained constant up to eight months of storage.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations